WACANA DALAM PERSPEKTIF NORMAN FAIRCLOUGH - Hamdan Hamdan (Jurnal Komodifikasi, 2019)
This paper focuses its discussion on the issue of discourse in the perspective of Norman Fairclough. There are two major paradigms that underlie various perspectives in the study of discourse analysis, namely the formalist paradigm and the functional paradigm. The first view discourse is better understood and positioned as the largest unit of the linguistic unit, and separate from its social context. The second view discourse as specific focuses related to the function or use of language and become an integral part of its social context. Norman Fairclough built a middle ground and formulated a form of discourse analysis that referred to the critical paradigm. In a discourse production, it is always followed gradually by the production of identity, class production, ideological production, and power production. Discourse for Fairclough is an important form of social practice that reproduces and changes knowledge, identity, and social relations which include power relations, and at the same time formed by other social structures and practices.